Legal Certainty in The Preparation of Notarial Deeds By Appearers With Disabilities Who Are Unable to Sign - Ramadhanty, Savira; Budianto, Agus; Soerodjo, Irawan (Journal of Law, Politic and Humanities, 2026)
Authentic deeds drawn up by Notaries as public officials with the authority to do so, with strict legal formalities and superior evidentiary power. In its application, the certainty of signatures and/or fingerprints by appearers with disabilities in deeds is questionable, as this has not been strictly regulated in the Law No. 30 of 2004 on Notary Position as partially amended by Law No. 2 of 2014 on Amendments to Law No. 30 of 2004 on Notary Position (“NOTARY OFFICIAL LAW”). The issues raised in this article are: How can legal certainty be ensured for persons with disabilities who are unable to sign and/or provide fingerprints before Notaries? And what is the ideal arrangement for persons with disabilities who are unable to sign and/or provide fingerprints before Notaries? The research method used is normative legal research, a type of research commonly conducted in the development of legal science, namely Legal Dogmatics ( rechtsdogmatiek ). The approach used is laws and regulations. The results of the study show that signatures cannot be affixed. According to the NOTARY OFFICIAL LAW, the reason for the inability to affix signatures must be stated clearly and explicitly at the end of the deeds. If the deeds cannot be signed and the Notaries do not provide a clear and explicit reason at the end of the deeds, this can reduce the probative value of the deeds to that of private deeds and will provide grounds for the aggrieved party to claim cancellation of deeds. Of course, rules such as these will not work if legal certainty is not incorporated into the resulting law. Furthermore, if problems arise in the future on the voidable deeds, Notaries cannot be held criminally liable simply for recording the information requested by the parties. In this regard, it is necessary to improve the regulations for implementing the provisions of Article 44 of the Notary Position Law to ensure that appearers with physical disabilities who have limited hand use can still perform legal actions before Notaries.